The Effect of WFH, Position Specifications on Employee Satisfaction and Its Impact on Employee Performance PT Titis Sampurna - O&M Prabumulih - Sudarta, Sudarta (Marcha Institute, 2023)
This study aims to determine the effect of work from home (WFH), job specifications on employee work and its impact on the performance of PT. Titis Sampurna – Operation & Maintenance of Prabumulih. The type of research used is associative research. The technique of collecting data in this research is by distributing questionnaires. The research population at PT. Titis Sampurna O & M Prabumulih opened 156 employees and a sample of 112 employees. Analysis of the data used in this study is inferential statistical analysis with a path analysis approach, with a significant level of 5%. The results showed that 1) There was a positive and significant effect of Work From Home (WFH) on the Job Satisfaction of PT. Titis Sampurna O & M Prabumulih, 2) There is a positive and significant influence of Job Specifications on the Work of Employees of PT. Titis Sampurna O & M Prabumulih, 3) There is a positive and significant effect of Work From Home (WFH) on the performance of employees of PT. Titis Sampurna O & M Prabumulih, 4) There is no and significant effect on the performance of employees of PT. Titis Sampurna O & M Prabumulih, 5) There is a positive and insignificant effect of Work from Home (WFH), Job Specifications on Employee Performance through Employee Work objectives as Intervening Variables PT. Titis Sampurna O & M Prabumulih.